Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to SJRCC Volume 18, Number 1, the first of four issues planned in 2019. In this issue we provide the usual varied selection of peer-reviewed articles, commentaries and book reviews.